Immunomodulatory Effects of Mesenchymal Stem Cell Secretome in Systemic Lupus Erythematosus: A Meta-Analysis - Narisa Felinka Kusuma; Nova Kurniati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by immune system dysregulation and multi-organ damage. Mesenchymal stem cells (MSCs) have emerged as a promising therapeutic option due to their immunomodulatory properties, primarily mediated through their secretome (MSCS). This meta-analysis aimed to evaluate the efficacy and safety of MSCS in SLE patients. Methods: A systematic search of PubMed, Embase, and Web of Science was conducted for studies published between 2013 and 2024 investigating the effects of MSCS in SLE. Randomized controlled trials (RCTs) comparing MSCS with placebo or standard care were included. The primary outcome was SLE disease activity, assessed using the SLE Disease Activity Index (SLEDAI). Secondary outcomes included immunological markers (e.g., anti-dsDNA antibodies, complement levels), quality of life, and adverse events. Data were pooled using a random-effects model. Results: Nine RCTs (n=485 patients) met the inclusion criteria. MSCS therapy significantly reduced SLEDAI scores compared to controls (standardized mean difference [SMD] -0.78, 95% CI -1.25 to -0.31, p=0.001). Significant improvements were also observed in anti-dsDNA antibody levels (SMD -0.62, 95% CI -1.01 to -0.23, p=0.002) and complement C3 levels (SMD 0.55, 95% CI 0.21 to 0.89, p=0.002). MSCS was generally well-tolerated, with no serious adverse events reported. Conclusion: This meta-analysis demonstrates that MSCS therapy has significant immunomodulatory effects in SLE, leading to improved disease activity and immunological profiles. Larger, well-designed RCTs with longer follow-up periods are needed to confirm these findings and assess the long-term efficacy and safety of MSCS in SLE.